Cerebrovascular Disease and Cognitive Outcome in Patients with Cardiac Disease - Johansen, Michelle C.; Gottesman, Rebecca F. (Seminars in Neurology, 2021)
The pace of understanding cognitive decline and dementia has rapidly accelerated over the past decade, with constantly evolving insights into the vascular contributions to cognitive impairment and dementia (VCID). Notably, more overlap has been discovered in the pathophysiology between what was previously understood to be Alzheimer's disease and VCID, leading to a heightened emphasis on disease prevention through early and aggressive control of vascular risk factors. One particularly vulnerable population may be those with cardiac disease, as they are at risk for cerebrovascular disease, which itself can lead to dementia, and increasing evidence supports cognitive impairment in disease processes such as heart failure and atrial fibrillation, independent of ischemic stroke, suggesting other potential mechanisms. In this article, we review the evidence supporting the relationship between cardiac disease, cerebrovascular disease, and cognitive decline and discuss the ongoing and future research efforts aimed at defining the important relationship between these entities.
Keywords: cognition; dementia; cardiac disease; infarct; white matter disease